Porting SIMRJGSA Algorithms For Mapping And Alignment To Malay-English Bitexts. - AI-Adhaileh, Mosleh H.; Tang, Enya Kong; Melamed, I. Dan (2001)

(untitled)
Parallel texts or Bitexts - where the same content is available in several languages, due to document translation, are becoming plentiful and available, both in private data warehouses and on publicly accessible sites on the WWW.